APPLICATION OF FE3AL INTERMETALLIC PHASE FILLER METAL IN VALVE SEATING FACE HARD FACING - Bożena SZCZUCKA-LASOTA; Tomasz WĘGRZYN; Piotr CYBULKO (Scientific Journal of Silesian University of Technology. Series Transport)
The exhaust valve seat face is a surface that degrades slowly as a result of mechanical and thermal stresses. There is extensive research on new materials for valves and for the improvement of valve production technology. This paper discusses the method of obtaining a filler metal made of Fe3Al intermetallic phase and the method of TIG hard-facing on a valve seating face made of H9S2 steel, evaluating the effects of essential hard-facing parameters. The resulting hard-facing build up was assessed in terms of quality using industrial radiography testing (RT).